Measurement of insulin-like growth factor axis does not enhance specificity of PSA-based prostate cancer screening. - Oliver, SE; Holly, J; Peters, T; Donovan, J; Persad, R; Gillatt, D; Pearce, A; Hamdy, F; Neal, D; Gunnell, D (2004)
OBJECTIVES: To examine whether measurement of insulin-like growth factor (IGF)-I, IGF-II, IGF binding protein (IGFBP)-2 or IGFBP-3, alone or in combination, enhanced the specificity of prostate cancer detection among men with a prostate-specific antigen (PSA) level of 3 ng/mL or greater beyond that achieved by the free/total PSA index. METHODS: Cross-sectional analysis was performed on blood samples taken from 597 asymptomatic men (79% of those biopsied) participating in a community case-finding exercise. All men had a total PSA level of 3 ng/mL or greater and had undergone prostate biopsy. Assays of IGF-I, IGF-II, IGFBP-2, IGFBP-3, and free and total PSA were performed. The predictive performance of a range of measures was assessed using receiver operating characteristic analyses and compared with the free/total PSA index, for all biopsies and for men with a PSA level of 3 to 10 ng/mL. The overall test performance was summarized using the area under the receiver operating characteristic curve (AUC). RESULTS: Of the 597 men, 185 (31.0%) had prostate cancer identified at biopsy. When all biopsies were included, the performance of the free/total PSA index (AUC 0.73) was significantly greater than for IGF-I (AUC 0.59; P <0.0001), IGF-I/PSA ratio (AUC 0.65; P = 0.002), IGF-I + IGFBP-3 (AUC 0.59; P <0.0001), IGF-II (AUC 0.66; P = 0.002), and IGF-II + IGFBP-3 (AUC 0.67; P = 0.05). The combined measurement of free/total PSA, IGF-II, and IGFBP-3 resulted in a slight improvement in performance (AUC 0.76; P = 0.01). The results were similar when the analyses were restricted to men with an initial PSA level of 3 to 10 ng/mL. CONCLUSIONS: We found no evidence that measurement of the IGF axis enhances the specificity of prostate cancer detection in clinical practice beyond that achievable using the free/total PSA index.